An Estimate of the Standard of Living in China - Dittmer, C. G. (Quarterly Journal of Economics, 1918)
I. Purpose: bearing on other investigations and an example of real economic pressure, 107. — II. Source of data: investigations made at Tsing Hua College, Peking, China, 108. — III. Limitations: an intensive survey of one district and not necessarily typical of the whole country, 110. — IV. Classes represented: Chinese and Manchu villagers, 112. — V. Tables: five tables classifying incomes, average amount expended for various purposes, per cent expended for various purposes, and sundry other items by expenditure groups, 113. — VI. Analysis of tables, 119. — VII. General conclusions, 122. — VIII. Comparison with other investigations: Engel, Mrs. More, Chapin, and the United States Bureau of Labor, 123. — IX. How it is done: the maintenance of a starvation standard, 124. — X. The cost, 127. — Figure I: a comparison of the extremes of variation in the percentage of expenditure for various purposes between the highest and the lowest income groups in five well known investigations, 123. — Figure II: a comparison of the percentage and average expenditures of 195 Chinese and Manchu families, 126.